2017
DOI: 10.1093/chemse/bjw126
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Oral Sweet Taste Sensation with Gymnema sylvestre Affects Postprandial Gastrointestinal Blood Flow and Gastric Emptying in Humans

Abstract: An oral sweet taste sensation (OSTS) exaggerates digestive activation transiently, but whether it has a role after swallowing a meal is not known. Gymnema sylvestre (GS) can inhibit the OSTS in humans. We explored the effect of the OSTS of glucose intake on gastrointestinal blood flow, gastric emptying, blood-glucose, and plasma-insulin responses during the postprandial phase. Eight participants ingested 200 g (50 g × 4 times) of 15% glucose solution containing 100 mg of 13C-sodium acetate after rinsing with 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…Six healthy males and nine healthy females (mean age 22 ± 3 years; mean height 162 ± 11 cm; mean weight, 56 ± 9 kg; mean body mass index (BMI), 21.2 ± 2.4 kg/m 2 ) were included in the study. To determine the total sample size required in this study, we compared gastric emptying index (i.e., Tmax -calc ) between two groups with or without rinsing GS solution using G*Power software (version 3.1.9.2) [12]. We obtained an effect size of 1.24 for a critical t of 2.365 at α of 0.05 and power (1 − β) of 0.80.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Six healthy males and nine healthy females (mean age 22 ± 3 years; mean height 162 ± 11 cm; mean weight, 56 ± 9 kg; mean body mass index (BMI), 21.2 ± 2.4 kg/m 2 ) were included in the study. To determine the total sample size required in this study, we compared gastric emptying index (i.e., Tmax -calc ) between two groups with or without rinsing GS solution using G*Power software (version 3.1.9.2) [12]. We obtained an effect size of 1.24 for a critical t of 2.365 at α of 0.05 and power (1 − β) of 0.80.…”
Section: Participantsmentioning
confidence: 99%
“…GS is a plant able to selectively suppress the sweet taste sensation in humans [24,25]. We found that GS-dependent suppression of OSS during ingestion of pure glucose solution slowed gastric emptying rate and glycemic response [12,13]. However, it is unknown whether suppressing OSS during consumption of a real sweet food affects both sweet taste liking and CPRs.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The Doppler beam insonation angle was maintained at ≤60 • relative to the artery. A previously established methodology [3,7] was used to calculate the second-by-second MBV. First, the Doppler signals for antegrade and retrograde flows and the electrocardiogram signal were digitally sampled online at 20 kHz using an analog/digital converter (PowerLab 8/30, ADInstruments, Colorado Springs, CO, USA).…”
Section: Ge Rate and Gi Blood Flowmentioning
confidence: 99%
“…The celiac artery supplies blood to the stomach, pancreas, spleen, and liver, and the superior mesenteric artery primarily supplies blood to the jejunum and ileum [6]. Celiac artery BF and superior mesenteric artery BF both increase remarkably after macronutrient food consumption [7,8], and these responses support the various functions of the GI system (e.g., the motility and delivery of absorbed nutrients and the secretion of gut hormones) [6]. Thus, these previous results suggested that post-exercise GI hypoperfusion leads to acutely suppressing subsequent digestive and/or absorptive functions.…”
Section: Introductionmentioning
confidence: 99%